Reliability of Ultrasound for diagnosis of appendicitis in children - Mohajerzadeh, Leily; Khalili, Mitra; sarafi, Mehdi; Rafiei tabatabaei, Sedigheh; Harati, Mohammadreza (Iranian Journal of Pediatric Surgery, 2022)
Introduction: In the medical world, acute appendicitis is one of the common surgeries. The Aim of this study is determining reliability of ultrasound in acute appendicitis. Materials and Methods: The ethical code has been gotten in this research firstly. Based on the archives at Mofid Hospital, the list of appendectomy children in a six- months period has been extracted when they used the ultrasound prior to surgery. Demographic data, medical history and findings of appendicitis, even during the surgery, have been recorded using designed questionnaire based on patients’ documents. According to the surgeon report, not only have appendicitis patients been operated but also confirmed. The ultrasound results have been compared with surgical results (as the gold standard). For each of the ultrasound findings, based on SPSS software as has used for analyzing, some parameters have been calculated such as sensitivity index, specificity, positive and negative predictive value, accuracy and area under the ROC curve. Results: In this study, 111 children with diagnosis of appendicitis have been operated. Based on the ultrasound prior to surgery, 71 patients (64%) with purulent appendicitis showed direct sonographic signs of appendicitis, 11 patients (9.9%) showed indirect signs, 6 patients (5.4%) revealed complicated signs, 7 patients (6.3%) with mesenteric lymphadenopathy and 16 patients (14.4%) negative in ultrasound. Also, according to the final diagnosis after surgery, 105 patients (94.6%) had appendicitis and 6 people (5.4%) were negative for appendicitis. The significant relationship was found between the ultrasound results prior to surgery and the final diagnosis after surgery for patients (p<0.05). The diagnostic value of ultrasound results prior to surgery in order to determine the appendicitis in children undergoing surgery has been revealed by different factors such as sensitivity, specificity, positive predictive value, negative predictive value and accuracy . These factors are at 83.8%, 100%, 100%,83% and 92.3%, respectively (p< 0.05). Conclusion: It seems that Ultrasound prior to surgery is the useful method to determine the children appendicitis.